Maintenance optimisation through quality management: a case study in 'Alzinc' Plant in Algeria. (3rd May 2019) - Mami, Elias Fouad; Cheikh, Abdelmadjid; Kadi, Mohammed; Labadi, Karim
The aim of this paper is to apply the maintenance optimisation through quality management for a real-life industrial plant in Algeria, 'Alzinc' that have obtained various certifications (ISO 9001, ISO 14001) and is moving towards a new integrated management. The purpose consists of maintaining production activities without reducing the equipment efficiency as well as the quality of the products, the workers safety and the environment protection. In our study, maintenance optimisation combines two innovative and strategic methods, taking into account the social and cultural local background. In this case, it becomes crucial to identify indigenous culture specificities that could be integrated to universal strategic methods and techniques. Thus, our methodology relies upon the combination between reliability centred maintenance (RCM) and total productive maintenance (TPM), using the four first pillars with the aim of achieving a maximal efficiency of the production system (axis no. 1). Results show that our approach could be generalised to all the plant workshops, et allows the implementation of the other TPM pillars, in order to improve and secure the plant optimal production (axis no. 2).